Entrepreneurship and Economic Development: A Review of Conceptual and Theoretical Foundations - Meziani, Feyrouz; Bekhouche, Sarra (Journal of Ecohumanism, 2025)
The relationship between entrepreneurship and development is a critical topic today, as society searches for solutions that achieve development. In this context, this paper aims to examine the relationship between entrepreneurship and development by analyzing the concept of entrepreneurship and its role in achieving economic development. The research findings indicate that entrepreneurship is an essential part of the development support system.